2006
DOI: 10.1002/bjs.5323
|View full text |Cite
|
Sign up to set email alerts
|

Repeat hepatic resection for recurrent colorectal liver metastases is associated with favourable long-term survival

Abstract: The beneficial outcomes observed after repeat liver resection in selected patients with RCLM confirm the experience of others and support its status as the preferred choice of treatment for such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
2
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 24 publications
8
92
2
8
Order By: Relevance
“…These data agree with the conclusions of a recent meta-analysis of studies assessing repeat hepatectomy for recurrent CRLM [25]. While this earlier analysis found no significant difference in overall survival between the single resection and repeat resection groups when all studies were evaluated, repetition of analyses to include just high-quality studies [11,12,14,15] or just studies with greater than 500 cases demonstrated that repeat resection was significantly associated with improved overall survival following metastasectomy. In agreement with this, Saiura et al recently found the performance of repeat resection to be independently associated with prolonged overall survival following metastasectomy [26].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These data agree with the conclusions of a recent meta-analysis of studies assessing repeat hepatectomy for recurrent CRLM [25]. While this earlier analysis found no significant difference in overall survival between the single resection and repeat resection groups when all studies were evaluated, repetition of analyses to include just high-quality studies [11,12,14,15] or just studies with greater than 500 cases demonstrated that repeat resection was significantly associated with improved overall survival following metastasectomy. In agreement with this, Saiura et al recently found the performance of repeat resection to be independently associated with prolonged overall survival following metastasectomy [26].…”
Section: Discussionsupporting
confidence: 87%
“…Studies to date, however, have yielded conflicting results regarding the influence of repeat hepatectomy for CRLM upon longterm survival [11][12][13][14][15][16][17]. A notable finding of this study was that repeat hepatectomy was significantly associated with improved overall and cancer-specific survival following metastasectomy, along with established prognostic factors including tumor number and margin status.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Such a conservative and yet radical policy is vital in case of reduced liver functionality or in the presence of multiple lesions. Moreover, both in the case of primary and secondary liver tumors, maximizing the preservation of liver tissue not directly involved by the lesion increases the possibility of subsequent resections [2,27].…”
Section: Discussionmentioning
confidence: 99%